Geochemical Characteristics, Origin, and Evolution of Ore‐Forming Fluids of the Khut Copper Skarn Deposit, West of Yazd in Central Iran. Issue 3 (July 2014) - Zahedi, Azam; Boomeri, Mohammad; Nakashima, Kazuo; Mackizadeh, Mohammad Ali; Ban, Masao; Lentz, David R.
Abstract The Khut copper skarn deposit is located at about 50 km northwest of Taft City in Yazd province in the middle part of the Urumieh‐Dokhtar magmatic arc. Intrusion of granitoid of Oligocene–Miocene age into carbonate rocks of the Triassic Nayband Formation led to the formation of marble and a calcic skarn. The marble contains high grade Cu mineralization that occurs mainly as open space filling and replacement. Cu‐rich sulfide samples from the mineralized marble are also anomalous in Au, Zn, and Pb. In contrast, the calcic skarn is only weakly anomalous in Cu and W. The calcic skarn is divided into garnet skarn and garnet–pyroxene skarn zones. Paragenetic relationships and microthermometric data from fluid inclusions in garnet and calcite indicate that the compositional evolution of skarn minerals occurred in three main stages as follows. (i) The early prograde stage, which is characterized by Mg‐rich hedenbergite (Hd53.7Di42.3–Hd86.1Di9.5) with Al‐bearing andradite (69.8–99.5 mol% andradite). The temperature in the early prograde skarn varies from 400 to 500°C at 500 bar. (ii) The late prograde stage is manifested by almost pure andradite (96.2–98.4 mol% andradite). Based on the fluid inclusion data from garnet, fluid temperature and salinity in this stage is estimated to vary from 267 to 361°C and from 10.1 to 21.1 wt% NaCl equivalent, respectively. Pyrrhotite precipitation started during this stage. (iii) The retrograde stage occurs in an exoskarn, which consists of an assemblage of ferro‐actinolite, quartz, calcite, epidote, chlorite, sphalerite, pyrite, and chalcopyrite that partially replaces earlier mineral assemblages under hydrostatic conditions during fracturing of the early skarn. Fluids in calcite yielded lower temperatures (T < 260°C) and fluid salinity declined to ∼8 wt% NaCl equivalent. The last stage mineralization in the deposit is supergene weathering/alteration represented by the formation of iron hydroxide, Cu‐carbonate, clay minerals, and calcite. Sulfur isotope data of chalcopyrite (δ34S of +1.4 to +5.2‰) show an igneous sulfur source. Mineralogy and mineral compositions of the prograde assemblage of the Khut skarn are consistent with deposition under intermediately oxidized and slightly lower fS2 conditions at shallow crustal levels compared with those of other typical Fe‐bearing Cu–Au skarn systems.